Enhancing Student Interest through Collaborative School-Based Marketing - Nio Nilasari; Muhammad Thoyib; Dhinuk Puspita Kirana (Excelencia: Journal of Islamic Education & Management, 2025)
In today's globalized world, where educational institutions face intense competition, schools must adopt professional marketing strategies that go beyond academic excellence. Educational marketing has become a vital tool for institutions to establish a strong presence, build a positive reputation, and attract prospective students and parents. One innovative approach gaining traction is the collaborative school concept, which involves partnerships between schools and various stakeholders to enhance quality and appeal. This study explores the implementation of an educational marketing strategy based on the collaborative school approach at SMA Negeri 3 Ponorogo, aiming to increase interest among prospective students. Our research focuses on the 4P marketing mix concept – product, place, price, and promotion – integrated to promote the school's flagship program, the Smaga International Class Program (SICP). Additionally, we examine market segmentation, school positioning, marketing communication, and educational services as collaborative efforts between the school, community, and stakeholders. Using a descriptive qualitative approach, we collected data through interviews, observations, and documentation. The results show that a systematic and collaborative marketing strategy has successfully boosted the school's competitiveness, strengthened its institutional image, and attracted prospective students more effectively. Therefore, the collaborative school approach is a relevant alternative in educational marketing strategies, addressing the dynamic needs and challenges of education in the global era